G20 Country Rating System in Handling Covid-19 Using the Hybrid AHP-TOPSIS Method - Fandhika Bayu Fitri; Setyawan Wibisono (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Covid-19 is a new type of infectious virus that attacks the respiratory tract. The process of spreading the virus is fast, making some countries implement several policies such as regional quarantine and social distancing. However, due to limited human activities in various countries it has an impact on the global economic downturn. The magnitude of the impact of Covid-19 on humans and the world economy, made the G20 member countries agree to cooperate to accelerate global economic recovery. Organization. The G20 is an international forum whose members are from the world's developed economies that focus on discussing important issues of the world economy. Even though it contains developed economies, cases of Covid-19 are still high in several member countries of the G20 organization. Based on the condition of the high number of Covid-19 cases in the G20 member countries, this study aims to build a ranking system for the G20 countries in handling Covid-19 using the Analytic Hierarchy Process (AHP) method for the weighting process of criteria and the Technique for Order Preference by method. Similarity to Ideal Solution (TOPSIS) for alternative ranking process. In the implementation of the AHP method, the weight of each criterion is obtained as follows: the number of testing ratio is 0.545274265, the ratio of the number of cured is 0.24396228, the ratio of positive numbers is 0.156108929 and the ratio of the number of deaths is 0.054654525. The results of the weighted criteria that have been calculated, the TOPSIS method is used for the alternative ranking process. The results of the highest preference value are obtained by the 6th alternative with a preference value of 0.825108653.